Nilai-nilai Pendidikan Optimisme pada Tradisi Tedhak siten di Masyarakat Jawa - Anwar Hafidzi (Mahesa Research Center, 2020)
This study aims to uncover the meaning behind the tedhak siten tradition and its relationship to the changes and structure of life in society. Although there are many studies that discuss this from its philosophical values, there is no character value that discusses it. These findings at least prove that tradition can provide a positive value in social life. This study uses descriptive-qualitative research with primary data researchers obtained from interviews and observations during the procession of Tedhak siten ceremony in Tanah Laut, South Kalimantan. The results of this study prove that the tedhak siten tradition practiced by the Javanese people still adopts Islamic teachings. The ceremony has a meaning related to the formation of the child's character, changes in attitude and self in life in society in the future. This tradition tends to bring up the values of goodness in the form of patterns of alms, giving thanks, praying, and being hopeful. This theory tends to be called Education optimism about what will and will be achieved later.